A Comprehensive Analysis on Vowels Present in Bodo Language - Sharma, Uzzal (International Journal of Computer Sciences and Engineering, 2015)
Research on Speech signal processing has gained a high degree of importance due to the broad areas of application. The success of any speech recognition system and speaker identification system depends on the level of accuracy and correctness. To accomplish a high level of accuracy, it is very important to use the proper tool for the purpose. The present paper tries to use two popular tools namely MFCC and Formant Frequency Measure used for the purpose of feature extraction and to give a comparison between the two. The Bodo language is considered for the present research.